2015
DOI: 10.3233/ch-141862
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inflammatory and lipidic parameters on red blood cell distribution width in a healthy population

Abstract: Red blood cell distribution width (RDW) is a routine red blood cell count parameter which has been shown to be associated with inflammatory parameters. Recently, some authors proposed that RDW seems to be a marker of an adverse lipidic profile. In order to clarify whether RDW is related to inflammation, plasma lipids, or both, we determined anthropometric, hematimetric, inflammatory and lipidic parameters in 1111 healthy subjects. RDW correlated directly with age, body mass index (BMI), inflammatory parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 24 publications
7
50
2
Order By: Relevance
“…However, we did not find a correlation between AIP, T cholesterol, and RDW in our patients, which is in agreement with Vaya et al [13]'s study. They also did not observe a correlation between RDW and T cholesterol, HDL-C, LDL cholesterol, or TG in a healthy Mediterranean population [13]. They found that RDW is associated with inflammatory markers but not with an unfavourable lipid profile.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, we did not find a correlation between AIP, T cholesterol, and RDW in our patients, which is in agreement with Vaya et al [13]'s study. They also did not observe a correlation between RDW and T cholesterol, HDL-C, LDL cholesterol, or TG in a healthy Mediterranean population [13]. They found that RDW is associated with inflammatory markers but not with an unfavourable lipid profile.…”
Section: Discussionsupporting
confidence: 82%
“…Increases in erythrocyte membrane cholesterol levels are responsible for the deterioration of cell deformability, which affects the lifespans of circulating erythrocytes, and this results in elevated RDW values [13,17,18]. However, we did not find a correlation between AIP, T cholesterol, and RDW in our patients, which is in agreement with Vaya et al [13]'s study. They also did not observe a correlation between RDW and T cholesterol, HDL-C, LDL cholesterol, or TG in a healthy Mediterranean population [13].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Neutrophil-lymphocyte ratio (NLR), an easily obtainable inflammatory marker, is also proved to be associated with the prognosis of HCC (19). Previous studies indicated that RDW is positively correlated with inflammatory biomarkers, such as CRP and erythrocyte sedimentation rate (ESR) in unselected outpatient (20) and healthy population (21). It can, hence, be hypothesized that RDW may be indicator of inflammation.…”
Section: Proposed Mechanisms In Role Of Rdw In Hccmentioning
confidence: 99%